2014
DOI: 10.3899/jrheum.140651
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100A12 May Be a Useful Biomarker of Disease Activity in Adult-onset Still’s Disease

Abstract: S100A12 levels showed strong correlations with known disease activity markers such as ESR, CRP, ferritin, and systemic score. In the followup patients with AOSD, most patients showed decreased S100A12 levels after resolution of disease activity. These results suggest that serum S100A12 can be a reliable clinical marker for monitoring disease activity and treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Thus far, many studies have shown correlations between serum S100A12 and the prognoses of some inflammatory diseases, as well as between serum S100A12 and the activity of these diseases. 20,21 The findings of the present study suggest that S100A12 levels are correlated with the prognosis and severity of DM-ILD.…”
Section: Discussionsupporting
confidence: 51%
“…Thus far, many studies have shown correlations between serum S100A12 and the prognoses of some inflammatory diseases, as well as between serum S100A12 and the activity of these diseases. 20,21 The findings of the present study suggest that S100A12 levels are correlated with the prognosis and severity of DM-ILD.…”
Section: Discussionsupporting
confidence: 51%
“…Later on, such results were confirmed and a positive correlation of S100A8/A9 with leukocyte count, ESR, CRP, ferritin, systemic disease score and also a decrease after disease activity status resolution were detected [85]. More recently, a correlation with disease activity, serological markers (ESR, CRP, ferritin) and systemic score was described for the S100A12 protein too [86].…”
Section: S100a8 A9 A12mentioning
confidence: 82%
“…[60] S100A8/A9 11,770 ± 8840 ng/ml 36 [85] 57.11 ± 25.38 ng/ml 25 [84] 0.5-9 ng/ml 18 [35] S100A12 547.9 ± 148.4 ng/ml 37 [86] Procalcitonin 0.09-71 ng/ml 5 [70] 2-10 ng/ml 1 [72] 0-1.4 ng/ml 38 [73] SD: Standard deviations.…”
Section: Biomarkersmentioning
confidence: 99%
“…Accumulating evidence has disclosed high levels of several inflammatory mediators including C-reactive protein, which are present at very high levels in the peripheral blood of patients at risk of POD or POCD (Cerejeira et al, 2012;Neerland et al, 2016;Vasunilashorn et al, 2017). It is confirmed initially that human S100A12 is expressed and secreted by activated neutrophil granulocytes (Achouiti et al, 2013;Bae et al, 2014;He et al, 2015;Isoyama et al, 2015Isoyama et al, , 2016Zhao et al, 2013). In this regard, S100A12 is known to trigger a pro-inflammatory immune response by binding RAGE, thereby leading to inflammatory activation (Achouiti et al, 2013;Bae et al, 2014;He et al, 2015;Isoyama et al, 2015Isoyama et al, , 2016Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 97%